Editorial (Jonathan Edwards studies, 2016)
We are pleased to commence the sixth year of the Jonathan Edwards Studies online journal, and continue to be encouraged by the reception and review of the journal and by the contributions we have received from scholars and researchers from all fields, specialists and generalists alike. It is the continuing mission of this journal to present all aspects of Edwards Studies, and more, to encourage inquiry and engagement of Edwards and his context.This issue contains articles on a range of topics, including Edwards on the humanity of Christ, Locke and Religious Affections, and primary source documents, including a recently found letter in the Angus Library, Regent's Park College,University of Oxford.